Critical Race Mixed Methodology (CRMM) as a transformative method: The benefits and challenges - Jessica T. DeCuir-Gunby; Whitney N. McCoy; Saba L. Modaressi (Methods in Psychology)
Critical Race Mixed Methodology (CRMM) is a transformative mixed methods approach that combines CRT within a mixed methods design. In this article, we reflect upon our experience using and publishing a CRMM explanatory mixed methods study in a higher education journal's special issue focused on mixed methods research. We discuss the benefits of using CRMM as a transformative method. Then, we share the challenges of using CRMM. We also provide recommendations for engaging in CRMM research within psychology.